Understanding BDA-AI Adoption in E-Commerce: An Integrated Framework of TOE and Technology Acceptance - Khan, Asif; Hung, Chung-Wen (Universitas Negeri Padang, 2025)
This study develops an integrated theoretical framework examining the adoption and acceptance of Big Data Analytics and Artificial Intelligence (BDA-AI) in e-commerce environments. By synthesizing the Technology-Organization-Environment (TOE) framework with the Technology Acceptance Model (TAM), this research examines how technological and environmental contexts influence the adoption of BDA-AI and subsequent user behavior. The framework proposes that contextual factors affect BDA-AI implementation, which in turn influences users’ perceived ease of use and perceived usefulness. These perceptions, along with user satisfaction, ultimately determine the intention to continue using BDA-AI-enabled e-commerce platforms. Through a comprehensive literature review spanning 2014-2025, this study establishes theoretical foundations for understanding AI adoption patterns in digital commerce. The research contributes to existing literature by: (1) conceptualizing BDA-AI as a unified technological construct, examining the interplay between external contexts and user acceptance factors, (2) providing a validated research instrument for future empirical investigations. For practitioners, this study offers strategic insights into implementing AI solutions that enhance user experience while maintaining competitive advantage in digital marketplaces.